(untitled) (European Journal of Pure and Applied Mathematics, 2023)
We define hesitant fuzzy maximal open cover to establish hesitant fuzzy m-compactness and discuss its properties. Further we obtain few more results on hesitant fuzzy minimal c-regular and minimal c-normal spaces. We have proved that a hesitant fuzzy Haussdorff m-compact space is hesitant fuzzy minimal c-normal.